Temporal trends in cardiovascular health among Chinese urban children and adolescents, 2004–2019 pre-pandemic COVID-19 - Xiao, Pei; Cheng, Hong; Yan, Yinkun; Hou, Dongqing; Dong, Hongbo; Zhao, Xiaoyuan; Mi, Jie (Frontiers in Public Health, 2022)
Objective Little is known about pre-pandemic cardiovascular health (CVH) status and its temporal variation in Chinese children. Thus, we aimed to evaluate the secular trends and associated factors of CVH in Chinese urban children from 2004 to 2019. Methods, We identified 32 586 individuals in Beijing, aged 6 to 18 years, from three independent cross-sectional studies conducted in 2004, 2014, and 2019, respectively. CVH was assessed by 7 metrics according to American Heart Association criteria, including smoking, physical activity, diet, body mass index, total cholesterol, blood pressure, and fasting glucose. Multivariable logistic regression was used to assess the association between sociodemographic characteristics and the ideal CVH status. Results The proportion of ideal CVH was decreased from 27.7% (boys 26.6%, girls 28.9%) in 2004 to 4.2% (boys 3.8%, girls 4.8%) in 2014, and then increased to 16.2% (boys 13.5%, girls 18.9%) in 2019. Overall, ideal smoking was the most prevalent CVH component during 2004-2019 (2004, 97.5%; 2014, 92.9%; 2019, 98.0%), while ideal physical activity (2004, 27.6%; 2014, 14.4%; 2019, 28.0%) and dietary intake (2004, 26.0%; 2014, 10.7%; 2019, 23.5%) were the least prevalent components. Notably, the proportion of ideal body mass index (2004, 77.5%; 2019, 59.7%) and blood pressure (2004, 73.6%; 2019, 67.3%) were continuously decreased from 2004 to 2019. Girls, parental normal weight status, free of family CVD history, and lower levels of fat mass were associated with higher odds of ideal CVH. Conclusion The cardiovascular health in Chinese urban children deteriorated during 2004-2019. Distinct strategies are required to mitigate socioeconomic inequity in the intervention of CVH promotion.